Antimycobacterial mechanism of vanillin involves disruption of cell-surface integrity, virulence attributes, and iron homeostasis. Issue 4 (December 2016) - Sharma, Sharda; Pal, Rahul; Hameed, Saif; Fatima, Zeeshan
Abstract: Objective/Background: Tuberculosis (TB) remains a global threat, claiming one-third of the population annually. The ever increasing emergence of multidrug-resistant TB (MDR-TB) is the major impediment to effective anti-TB therapy. Under such circumstances, deciphering the antimycobacterial potential of natural compounds has gained considerable prominence. This study evaluated the antimycobacterial activity of vanillin (Van), a natural food-flavoring agent and preservative, along with its potential mechanisms of action. Methods: Drug susceptibilities were performed using broth microdilution, spot, and filter-disc assays. Membrane damage was studied by nitrocefin hydrolysis and electron microscopy. Virulence attributes were assessed by biofilm formation and cell adherence. Iron availability was estimated by enzymatic (ferroxidase) assay. Results: We found that the antimycobacterial activity of Van against Mycobacterium smegmatis (a surrogate of Mycobacterium tuberculosis ) is 125 μg/mL. Additionally, we observed disruption of membrane homeostasis in the presence of Van, as revealed by enhanced membrane permeability and transmission electron microscopy images showing a disturbed cell envelope. Concomitant with our findings, we also observed that Van leads to enhanced drug susceptibility to membrane targeting known anti-TB drugs. Furthermore, Van affects significant virulence traits of Mycobacterium by inhibiting biofilm formation and cell adhesion. Finally, we observed that Van disrupted iron homeostasis as displayed by hypersensitivity to iron deprivation. Conclusion: The results established for the first time that Van could be an effective antimycobacterial agent that could be exploited further in treating mycobacterial infections.